As x and y ranges over all real values, what is the minimum value of
( 1 5 x + 3 0 y + 2 0 ) 2 + ( 2 0 x + 4 0 y + 1 5 ) 2 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great job!
Sorry, can this been found by calculus?
Richtig, Ja.
The minimum is 49: To find the minimum, we can take the partial derivatives of f ( x ) = ( 1 5 x + 3 0 y + 2 0 ) 2 + ( 2 0 x + 4 0 y + 1 5 ) 2 with respect to x and y and set them equal to zero. This gives: ∂ x ∂ f = 2 ∗ 1 5 ∗ ( 1 5 x + 3 0 y + 2 0 ) + 2 ∗ 1 0 ∗ ( 2 0 x + 4 0 y + 1 5 ) = 0 ∂ y ∂ f = 2 ∗ 3 0 ∗ ( 1 5 x + 3 0 y + 2 0 ) + 2 ∗ 4 0 ∗ ( 2 0 x + 4 0 y + 1 5 ) = 0 Further simplification yields a single equation: x + 2 y = − 2 5 2 4 or 2 y = − x − 2 5 2 4 Plugging this into the original function gives f ( x ) = ( 5 2 8 ) 2 + ( − 5 2 1 ) 2 = 2 5 1 2 2 5 = 4 9
If you take the partial derivatives then the f(
I naturally do this.
Rather, I do something similar.
We can partially factorize 1 5 x + 3 0 y + 2 0 = 1 5 ( x + 2 y ) + 2 0 and 2 0 x + 4 0 y + 1 5 = 2 0 ( x + 2 y ) + 1 5 . Since x , y ranges over all real values, x + 2 y can take on all real values; we can therefore replace x + 2 y as z . We need to find the minimum of ( 1 5 z + 2 0 ) 2 + ( 2 0 z + 1 5 ) 2 . Expanding and completing the square, we get ( 2 5 z + 2 4 ) 2 + 4 9 . The minimum ( 2 5 z + 2 4 ) 2 can be is 0 ; therefore, the minimum the whole thing can be is 4 9 .
Or, by Calculus, takes z=x+2y, get f(z), and put f'(z)=0, z=-25/24. Replace z in the f(z), and obtain 49.
Log in to reply
Right. But as for now I still don't know calculus so I'll have to do this.
[ 5 ( 3 x + 6 y + 4 ) ] 2 + [ 5 ( 4 x + 8 y + 3 ) ] 2
2 5 ( 3 x + 6 y + 4 ) 2 + 2 5 ( 4 x + 8 y + 3 ) 2
2 5 [ ( 3 x + 6 y + 4 ) 2 + ( 4 x + 8 y + 3 ) 2 ]
2 5 [ 3 ( x + 2 y ) + 4 ] 2 + [ 4 ( x + 2 y ) + 3 ] 2
2 5 [ ( 3 k + 4 ) 2 + ( 4 k + 3 ) 2 ]
Choose x + 2y = z So the given equation becomes: (15z + 20)^2 + (20z + 15)^2 = F(z) (Say) i.e. F(z) = 25z^2 + 48z + 9 .............(i) Differentiating F w.r.t. z & computing F'(z) = 0 we get z = - 24/25 Also F''(- 24/25) > 0 which means that the function attains it minima at z = - 24/25 So putting z = - 24/25 in (i) we get 49
Cool observation
The reason I could solve this problem was because the x and y coefficients have a common ratio (that is x:2y).
We find the lowest common multiple of the two expressions and we find that it is 6 0 x + 1 2 0 y
Let z = 6 0 x + 1 2 0 y then we can rewrite the expression as ( 4 z + 2 0 ) 2 + ( 3 z + 1 5 ) 2 .
Now we expand the expression and differentiate:
0 = d z d ( 1 4 4 2 5 z 2 + 2 0 z + 6 2 5 ) = 1 4 4 5 0 z + 2 0
1 4 4 5 0 z = − 2 0 ⟹ z = − 5 2 8 8
Therefore we substitute this value of z into our formula (as it will give us the minimum value):
( − 2 0 2 8 8 + 2 0 ) 2 + ( − 1 5 2 8 8 + 1 5 ) 2 = 4 9
So our answer is 4 9
Observe that
( 1 5 x + 3 0 y + 2 0 ) 2 + ( 2 0 x + 4 0 y + 1 5 ) 2 = ( 2 5 x + 5 0 y + 2 4 ) 2 + 4 9 .
But
( 2 5 x + 5 0 y + 2 4 ) 2 ≥ 0 .
Hence,
( 2 5 x + 5 0 y + 2 4 ) 2 + 4 9 ≥ 4 9 .
Which imlies that the minimum must be 4 9
( 1 5 x + 3 0 y + 2 0 ) 2 + ( 2 0 x + 4 0 y + 1 5 ) 2
Factorizing:
( 5 ( 3 x + 6 y + 4 ) ) 2 + ( 5 ( 4 x + 8 y + 3 ) ) 2
= 2 5 ( 3 x + 6 y + 4 ) 2 + 2 5 ( 4 x + 8 y + 3 ) 2
= 2 5 ( ( 3 x + 6 y + 4 ) 2 + ( 4 x + 8 y + 3 ) 2 )
In both equations, the x and (y) can be factorized into ( x + 2 y ) , giving
2 5 ( ( 3 ( x + 2 y ) + 4 ) 2 + ( 4 ( x + 2 y ) + 3 ) 2 )
We don't need to know the individual values of x and y , only the value of x + 2 y . Changing x + 2 y to a :
2 5 ( ( 3 a + 4 ) 2 + ( 4 a + 3 ) 2 )
Squaring:
2 5 ( 9 a 2 + 2 4 a + 1 6 + 1 6 a 2 + 2 4 a + 9 )
= 2 5 ( ( 2 5 a 2 + 4 8 a + 2 5 )
We now have a straightforward quadratic equation. To find the vertex, we find two a − v a l u e s that give the same result. 2 5 a 2 + 4 8 a = 0
a ( 2 5 a + 4 8 ) = 0
So a = 0 or 2 5 a + 4 8 = 0 this being a = − 2 5 4 8 . The vertex is at the value of a halfway between these two so a = − 2 2 5 4 8 = − 2 5 2 4
Putting this into the equation, we have:
2 5 ( 2 5 ( − 2 5 2 4 ) 2 + 4 8 ( − 2 5 2 4 ) + 2 5 )
2 5 ( 2 5 ( 2 5 2 4 ) ( 2 5 2 4 ) − 4 8 ( 2 5 2 4 ) + 2 5 )
2 5 ( 2 5 2 4 2 − 2 5 4 8 ( 2 4 ) + 2 5 )
= ( 2 4 2 − 4 8 ( 2 4 ) + 2 5 2 )
= ( 2 5 2 − 2 4 2 )
= ( 2 5 + 2 4 ) ( 2 5 − 2 4 )
= 4 9
$$\left(15x+30y+20\right)^2+\left(20x+40y+15\right)^2$$ $$=\left[15(x+2y)+20\right]^2+\left[20(x+2y)+15\right]^2$$ $$= \left(10^2+20^2\right)(x+2y)^2 + 2.600(x+2y)+625$$ $$= \left[25(x+2y)\right]^2 + 2.25.24(x+2y)+576+49$$ $$= \left[25(x+2y)+24\right]^2 + 49 \ge 49$$ $$\boxed{\text{My solution is 49}}$$
Note that ( 1 5 x + 3 0 y + 2 0 ) 2 + ( 2 0 x + 4 0 y + 1 5 ) 2 = 6 2 5 x 2 + 2 5 0 0 x y + 1 2 0 0 x + 2 5 0 0 y 2 + 2 4 0 0 y + 6 2 5 = ( 2 5 x + 5 0 y + 2 4 ) 2 + 4 9
Hence 4 9 is the answer.
We can see that ( 1 5 x + 3 0 y + 2 0 ) 2 + ( 2 0 x + 4 0 y + 1 5 ) 2 = ( 2 5 x + 5 0 y + 2 4 ) 2 + 4 9 Since, x , y ranges over all real numbers there are such pairs of ( x , y ) for which ( 2 5 x + 5 0 y + 2 4 ) 2 = 0 .
So, the minimum value of ( 1 5 x + 3 0 y + 2 0 ) 2 + ( 2 0 x + 4 0 y + 1 5 ) 2 = ( 2 5 x + 5 0 y + 2 4 ) 2 + 4 9 = 0 + 4 9 = 4 9
Consider a = 1 7 . 5 x + 3 5 y + 1 7 . 5 and b = 2 . 5 x + 5 y − 2 . 5
Let F be the function to minimise We see that F = ( a + b ) 2 + ( a − b ) 2
Also, by inspection a = 7 b + 3 5
Substituting for a and simplifying, we get F = 1 0 0 ( b 2 + 1 0 9 8 b + 2 4 9 )
= 1 0 0 ( ( b + 1 0 4 9 ) 2 + 2 4 9 − 1 0 2 4 0 1 )
This is minimum at b = − 4 9 / 1 0 (to make the square 0). Since b is linear in x and y , it can take this value.
Hence F m i n = 1 0 0 ( 2 4 9 − 1 0 0 2 4 0 1 ) which is 49
Let n = 5 x +10 y
f( n ) = (3 n +20)^2+(4 n +15)^2 = 25 n ^2+240 n +625
To find the minimum of a quadratic, we must find where the slope is 0, which is determined by solving for the derivative f'( n ) = 50 n +240; f'( n ) = 0 when n = -4.8
f(-4.8) = 25(-4.8)^2+240(-4.8)+625 = 576-1152+625 = 49
Okay so we start by expanding everything...
( 1 5 x + 3 0 y + 2 0 ) 2 + ( 2 0 x + 4 0 y + 1 5 ) 2 ⟹
6 2 5 x 2 + 2 5 0 0 x y + 1 2 0 0 x + 2 5 0 0 y 2 + 2 4 0 0 y + 6 2 5
Then we can subtract 49 (and then add it back) to make it factorable.
⟹ 6 2 5 x 2 + 2 5 0 0 x y + 1 2 0 0 x + 2 5 0 0 y 2 + 2 4 0 0 y + 5 7 6 + 4 9 ⟹ ( 2 5 x + 2 4 + 5 0 y ) 2 + 4 9
Well making the square value zero, we get 4 9 as our final answer.
And we factor it substituting a variable for (x+2y)...sorry that I didn't clarify that.
In order to find the minimum value of this function we can find where its derivative is equal to zero.
Expanding (15x+30y+20)^2 +(20x+40y+15)^2 out we get
625x^2 + 1200x + 2500xy + 2400y + 2500y^2 + 625
The work is kind of messy so I'm going to leave that out.
We want to find the derivative with respect to x and y. They turn out to be the same equation to work with when d/dx and d/dy = 0
So...
d/dx = 2(625x) + 1200 + 2500y = 1250x + 2500y + 1200 = 50(25x + 50y + 24)
Setting this equal to 0 we get
25x + 50y + 24 = 0
We need to find the intercept values of x and y when 25x + 50y = -24 y = (-24 - 25x)/(50)
x-intercept = -24/25 y-intercept = -24/50
Plugging x into the original equation and 0 for y we get 49. We also get 49 for substituting the y-intercept value and 0 for x.
(15(-24/25) + 20)^2 + (20(-24/25) + 15)^2 = 49
(30(-24/50) + 20)^2 + (40(-24/50) + 15)^2 = 49
É possivel resolver essa questão usando conhecimento de "matemática avançada". Basta chamar a expressão dada de z(x,y) e fazer as derivadas parciais em relação a x e y depois igualá-las à zero, após isso um sistema linear será encontrado e encontrar os valores de x e y que darão o valor mínimo de z(x,y) que serão x= -0.96 e y= 0.
Let the variable a = 15x + 30y. Then 20x + 40y is 4/3 a, and I am minimizing the sum of two quadratics in a, which is itself a quadratic in a. Since the coefficient of the quadratic term is positive, I know I'll find its minimum on the quadratic's axis of symmetry. The axis of symmetry is at a = -72/5. Putting this value of a into the quadratic gave me a minimum of 49.
TAKE 15 AND 20 OUT AND USE DIFFERENTIATION TO SOLVE PROBLEM
If you let x + 2y = z, then the expression becomes (15z+20)^2 + (20z+15)^2 which is 625z^2+1200z+625 Differentiate to get 1250z +1200 and the minimum value of this occurs when z = -24/25 Substitute back into expression to get value of 49
( 1 5 x + 3 0 y + 2 0 ) 2 + ( 2 0 x + 4 0 y + 1 5 ) 2
= 5 2 { ( 3 x + 6 y + 4 ) 2 + ( 4 x + 8 y + 3 ) 2 }
= 5 2 { 3 2 ( x + 2 y ) 2 + 4 2 + 2 4 ∗ ( x + 2 y ) + 4 2 ( x + 2 y ) + 3 2 + 2 4 ∗ ( x + 2 y ) }
= 5 2 { 5 2 ( x + 2 y ) 2 + 4 8 ( x + 2 y ) + 5 2 }
= 5 4 { ( x + 2 y + 5 2 2 4 ) 2 + 1 − 5 4 2 4 2 }
The minimum value is when x + 2 y + 5 2 2 4 is zero. So the minimum value is 5 4 ( 1 − 5 4 2 4 2 ) = 2 5 2 − 2 4 2 = 4 9 .
(15x+30y+20)^2 + (20x+40y+15)^2
= (15(x+2y)+20)^2 + (20(x+2y(+15)^2
(x+2y = a)
=(15a+20)^2 + (20a+15)^2
=625a^2 + 1200a + 625
= 25(25a^2 + 48a + 25)
f(x) = 25x^2 + 48x +25
f '(x) = 50x+48 = 0
x = -48/50
f ''(x) = 50 (is positive, hence the function only has only minima points - hence x=-48/50 is the minimum point) (that's how we say it in my language so it may sound strange)
if a=-48/50 then we got 25(23.04-46.08+25) = 49
can this be solved using trigonometry
Problem Loading...
Note Loading...
Set Loading...
Let a = 5 x + 1 0 y . Then the expression becomes ( 3 a + 2 0 ) 2 + ( 4 a + 1 5 ) 2 = 2 5 a 2 + 2 4 0 a + 6 2 5 = ( 5 a + 2 4 ) 2 + 4 9 ≥ 4 9 . Thus, the minimum is 4 9 .